Museu comunitário: proposta de restauro e reuso da residência de taipa do “Largo dos Inocentes” - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2017)
This work aims to elaborate a proposal for the restoration and reuse of a hand-made mud house located in "Largo dos Inocentes" (Macapá-AP), which presents in its immateriality the "know-how" constructive technique and the memories material. For the development of this research, the bibliographic review, oral history, cadastral survey and site diagnosis were used as methodology, which enabled the recognition of the value of the residence and served as support for the elaboration of the final proposal. As a final result of this, a proposal of restoration was elaborated with the ideal of preservation of this patrimony and the attribution of a new use based on the concept of Community Museum established by the Brazilian Institute of Museums (IBRAM), with the function of memory recognition and preservation , which in this case is linked to the constructive technique.
Keywords: Arquitetura - Restauração; Patrimônio cultural; Museu comunitário; CNPQ::CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO